Peran Ekonomi Kreatif Dalam Peningkatan Pendapatan Pengrajin Batik Tanjungbumi Ditinjau dari Perspektif Ekonomi Islam - Nur Faitdah; Abdur Rohman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to reveal the role of the creative economy in increasing the income of batik artisan in Tanjungbumi District, Bangkalan Regency. This study uses a descriptive qualitative approach with data collection methods through observation, interviews and documentation. The result of the study illustrate that the creative economy of written batik craftsmen in Tanjungbumi District, Bangkalan Regency is already good, it can be seen from the 15 craftsmen that 9 craftsmen have experienced an increase in income, 6 craftsmen with stable income from 2021 to 2022. Meanwhile, in an Islamic economic perspective, the craftsmen have fulfilled the production process, market and marketing, government policies, economic conditions, and partnerships, but have not met the management and financial indicators. Keywords: Creative Economi, Income, Handmade Batik, Islamic Economics